Early memories of warmth and safeness and eating psychopathology: The mediating role of social safeness and body appreciation - Oliveira, S. (2016)
Research on human development and functioning has highlighted the importance of early emotional and relational experiences. Particularly, an association between the absence of early positive memories and the presence of disordered eating has been evidenced by recent investigations. However, the mechanisms underlying this association remain unclear. Using a sample of 490 women, the hypothesis that early positive memories are negatively associated with disordered eating via social safeness and a positive relationship with one’s body image was tested via path analysis. The tested model explained 51% of eating psychopathology’s variance, and revealed a good adjustment to the empirical data. Additionally, social safeness and body appreciation were revealed as mediators of the impact of early warm and safe memories on disordered eating, when controlling for the effect of BMI. These findings suggest the importance of targeting social safeness and acceptance, especially when defining potentially effective programmes for the prevention of eating disorders.